Consumers perceptions towards the sponsorship of the 2006 FIFA World Cup - Russ, Florian (2006)
This qualitative study evaluates sports sponsorship from the football fans perspective, concentrating on the sponsorship of big sporting events and the FIFA World Cup in particular. The World Cup attracts billions of viewers and a huge number of companies intend to associate their products with this event, many organisations can be classified as ambushers due to the fact that they do not contribute financially to the event. The enormous corporate interest led to huge commercialisation of the event and FIFA introduced strict measures in order to prevent ambush marketing. This study researches commercialisations impact on fans attitudes and perceptions towards sponsorship. The literature review focuses among other aspects on two major frameworks developed by Speed and Thompson (2000) and Crimmins and Horn (1996) respectively. The framework developed by Speed and Thompson (2000) shows that brand-event fit and perceived sincerity of the sponsor are important determinants in order to evaluate sponsorship response. Crimmins and Horn (1996) argue that fans feel grateful for sponsors investment, which leads to sponsorships persuasive impact. These and other aspects are analysed and discussed by using 12 semi-structured interviews. The authors research shows that consumers are increasingly agitated by the growing commercialisation around an event such as the World Cup and they perceive sponsors to be insincere. So far fans still consider sponsorship to be important and are still grateful for a sponsors investment to a certain extent but practitioners have to be careful because the increasing exploitation could have damaging effects on brand image perceptions and sponsorship effectiveness. A conclusion chapter follows, which leads into a section incorporating limitations of the research methodology and offers managerial implications related to the topic area.